The politics of oil : controlling resources, governing markets and creating political conflicts - Claes, Dag Harald; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Exploring the wide variety of political aspects relating to oil resources and markets, The Politics of Oil provides an important and accessible introduction to topics such as the so-called 'resource curse', oil rent, producer cartels, and international oil governance. Broadening the scope further, Dag Harald Claes also examines the role of oil in political conflicts. Divided thematically into three parts, this book discusses the exercise of political control over oil resources, their extraction, and the income from oil exports; the vagaries of oil market forces and political attempts to govern them; and finally, the complex role of oil in international, regional, and domestic conflicts. Drawing on a number of academic perspectives, including economics, political science, philosophy, history, geology, and more, the key debates surrounding oil are explored. These include the role of OPEC, the future of oil in the context of climate change, and the part oil has played in civil war and terrorism. Easily accessible, this introduction to the intertwined relationship between oil and political decisions and behaviour, is an essential tool for students of political science, economics, and energy related studies of all kinds. It is also valuable for policy makers, industry practitioners, and others interested in the oil business or governance seeking a comprehensive introduction to the subject.
Contents: Part I Resource governance -- 1. Sovereignty and ownership -- 2. Governing oil production -- 3. Oil income- blessing or curse? -With Mads Motrøen -- Part II Market control -- 4. Institutional governance -- 5. Producer governance -- 6. OPEC -- Part III Political conflict -- 7. Oil and the US hegemony -- 8. Oil and regional security -- 9. Oil and domestic conflicts -- 10. Climate change and the future of oil -- Index.
Includes index.
Description based on print record.
Keywords: Offshore oil industry; Offshore oil industry -- Political aspects; Electronic books